Chapter Lo sviluppo della competenza lessicale: incursioni tra le ipotesi teoriche e le applicazioni glottodidattiche - Villarini, Andrea (Strumenti per la didattica e la ricerca, 2021)
The paper analyses the issue of the development of lexical competence in Italian as L2 learners. The notion of lexicon is considered from three different points of view: the point of view of the speaker/learner, the point of view of the researcher interested in language issues and the point of view of the foreign language teacher. The question of what to intend and how to manage the lexicon within a second language courses is an apparently trivial one that might be solved with a simple: "teaching Italian words"; while, it is one of the most rich of theoretical implications and methodological choices. This contribution aims at investigating the complex relationship between teaching language and lexicon, providing also a small list of instructions on how to teach the words of a new language for teachers of Italian language as L2.